Determination of postexcitation thresholds for single ultrasound contrast agent microbubbles using double passive cavitation detection - King, Daniel A. (Acoustical Society of America, 2010)
This work presents experimental responses of single ultrasound contrast agents to short, large amplitude pulses, characterized using double passive cavitation detection. In this technique, two matched, focused receive transducers were aligned orthogonally to capture the acoustic response of a microbubble from within the overlapping confocal region. The microbubbles were categorized according to a classification scheme based on the presence or absence of postexcitation signals, which are secondary broadband spikes following the principle oscillatory response of the ultrasound contrast agent and are indicative of the transient collapse of the microbubble. Experiments were conducted varying insonifying frequencies (0.9, 2.8, 4.6, and 7.1 MHz) and peak rarefactional pressures (200 kPa to 6.2 MPa) for two types of contrast agents (Definity(®) and Optison(™)). Results were fit using logistic regression analysis to define pressure thresholds where at least 5% and 50% of the microbubble populations collapsed for each frequency. These thresholds were found to occur at lower pressures for Definity than for Optison over the range of frequencies studied; additionally, the thresholds occurred at lower pressures with lower frequencies for both microbubble types in most cases, though this trend did not follow a mechanical index scaling.